2023
DOI: 10.3389/fpsyg.2023.1137220
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-esteem and mobile phone addiction among college students: The chain mediating effects of social avoidance and peer relationships

Abstract: IntroductionMobile phone addiction has a negative impact on the physical and mental health of college students, which has attracted extensive attention from scholars.MethodsIn this study, we investigated the mechanism of the influence of self-esteem on mobile phone addiction among 694 college students using the Self-Esteem Scale, the Mobile Phone. Addiction Scale, the Peer Relationship Scale and the Social Avoidance and Distress Scale.ResultsThe results showed that (1) self-esteem significantly and negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The findings reveal that external factors influence students' habitual behaviour on the utilisation of mobile phones for academic purposes. Previous research has demonstrated the effect of using mobile phones on individual behaviours (i.e., Ahmad, 2020;Chen et al, 2023;Fook & Narasuman, 2022;Li et al, 2020;Onaolapo & Oyewole, 2018;Reddy et al, 2023), this study presents a contrast from the previous study that employed the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. While the majority of the prior studies emphasised examining the factors that impact individual behavioural intentions towards technology usage (Alfalah, 2023;Rahi & Abd.…”
Section: Discussion and Suggestionsmentioning
confidence: 82%
See 1 more Smart Citation
“…The findings reveal that external factors influence students' habitual behaviour on the utilisation of mobile phones for academic purposes. Previous research has demonstrated the effect of using mobile phones on individual behaviours (i.e., Ahmad, 2020;Chen et al, 2023;Fook & Narasuman, 2022;Li et al, 2020;Onaolapo & Oyewole, 2018;Reddy et al, 2023), this study presents a contrast from the previous study that employed the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. While the majority of the prior studies emphasised examining the factors that impact individual behavioural intentions towards technology usage (Alfalah, 2023;Rahi & Abd.…”
Section: Discussion and Suggestionsmentioning
confidence: 82%
“…Students demonstrate a higher propensity to adopt and incorporate mobile phones into their academic practice when they receive encouragement and endorsement from both their peers and educators on the use of mobile phones for educational purposes (Chen et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen and Qin concluded that reducing loneliness and increasing selfesteem should be pursued in interventions aiming to reduce adolescents' social anxiety 19 . Chen and Shen's study showed that self-esteem is negatively related to MPA; when college students' self-esteem is high, it is di cult for them to fall into MPA 20 . Therefore, self-esteem may act as a mediator between depression and MPA.…”
Section: The Mediating Role Of Anxietymentioning
confidence: 99%
“…Prior research has confirmed that academic achievement is strongly linked to peer relationships [11,12]. For example, peer relationships can promote individuals' cooperation with others [3], enhance achievement motivation [13], influence course preferences [14], reduce cell phone addiction [15], and dissipate the negative effects of online education on academic engagement [16]. Having a trustworthy and loyal friend during the first semester of college was found to be associated with a higher grade point average (GPA) [17].…”
Section: Introductionmentioning
confidence: 99%